2021
DOI: 10.1002/mds.28611
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal α‐Synuclein Oligomers Reflect Disease Motor Severity in DeNoPa Longitudinal Cohort

Abstract: A BS TRACT: Background: Tangible efforts have been made to identify biomarkers for Parkinson's disease (PD) diagnosis and progression, with α-synuclein (α-syn) related biomarkers being at the forefront. Objectives: The objectives of this study were to explore whether cerebrospinal fluid (CSF) levels of total, oligomeric, phosphorylated Ser 129 α-synuclein, along with total tau, phosphorylated tau 181, and β-amyloid 1-42 are (1) informative as diagnostic markers for PD, (2) changed over disease progression, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 37 publications
2
23
0
Order By: Relevance
“…A number of studies measured α-syn levels from the blood and CSF. This was carried out also aiming at specific isoforms of α-syn (monomer vs. oligomers Miki et al 2018 ; Majbour et al 2021 ; soluble vs. insoluble Prigione et al 2010 ), which best characterize PD. The present study confirms a significant increase of α-syn levels, here measured using ultrastructural stoichiometry evidence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of studies measured α-syn levels from the blood and CSF. This was carried out also aiming at specific isoforms of α-syn (monomer vs. oligomers Miki et al 2018 ; Majbour et al 2021 ; soluble vs. insoluble Prigione et al 2010 ), which best characterize PD. The present study confirms a significant increase of α-syn levels, here measured using ultrastructural stoichiometry evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the last two decades probed the amount of α-syn in the blood, CSF and other fluids including saliva as a feasible marker in PD (Vivacqua et al 2016 ; Wang et al 2015 ). These studies became more and more elaborated in detecting specific protein conformation and providing a significant correlation between PD and specific isoform of α-syn in various fluids (Majbour et al 2021 ; Wang et al 2015 ; Graham et al 2019 ). Again, since α-syn accumulation is related to an impairment of its metabolism which mainly takes place via the autophagy machinery (Petroi et al 2012 ; Limanaqi et al 2020 ; Langston and Cookson 2020 ), autophagy-related proteins were measured in PD patients (e.g., Wu et al 2011 ; Miki et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the measurement of oligomeric α-Syn in biofluid has emerged as a promising approach to diagnose PD. Several studies have reported higher oligomeric α-Syn levels or ratio of oligomeric/total α-Syn in cerebrospinal fluid and red blood cells in PD patients than in healthy controls ( Tian et al, 2019 ; Majbour et al, 2021 ). Notably, oligomeric α-Syn were also detected in biofluids from healthy control individuals although at lower concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a number of drug candidates have been designed to interfere with the aggregation pathway aiming to eliminate existing oligomers or to prevent their formation 6 . Since aggregate formation reflects pathophysiological changes inside the brain, oligomers have also been proposed as promising biomarker candidates 7 9 . However, quantitative measurement of oligomers is technically challenging and mainly hampered by three technical issues.…”
Section: Introductionmentioning
confidence: 99%